Forensic Monitoring Project Report: Kamenica Exhumations Repubiika Srpska Commission on Missing and Tracing - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather On 31 July 1998 the Republika Srpska Commission on Missing and Tracing searched for bodies alleged to be buried on the grounds of a schoolhouse near the town of Kamenica. No human remains were encountered. Place of Exhumation: Kamenica Date of Exhumation: 31 July 1998 Minimum Number of Exhumed Individuals: 000